Implementation Law Issues Of Supreme Court Regulation No. 4 Of 2019 About Perma Revision No. 2 Of 2015 About Small Calim Court Resolution Procedures And Its Settlement Efforts - Tjoneng, Arman (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2020)
Legal dispute resolution can be done through non-litigation channels or through litigation channels. The non-litigation route as an alternative to dispute resolution (APS) outside the court route through its main mechanism, namely negotiation, mediation and arbitration, is increasingly loved by the public, especially the business world, because it offers various advantages compared to using the litigation route. But for some people, they still view dispute resolution through litigation as the main dispute resolution so that the consequence is that there is a buildup of cases in courts both at the first level, especially at the Supreme Court level. To anticipate this, the Supreme Court issued Perma No. 2015 concerning Procedures for Settlement of Small Claim Courts which was later revised to Perma No. 4 of 2019 concerning Amendment of Perma No. 2 of 2015 concerning Procedures for Settlement of Small Claim Courts. The Supreme Court's biggest hope is that this procedure can reduce the buildup of cases and can provide a sense of justice for the small community who demand justice, but in its implementation, there are still several legal problems that can cause the Small Claim Court to not run optimally. This study uses a normative juridical method supported by interviews. The primary data of this research are interviews with Supreme Court officials and several District Courts such as Central Jakarta District Court Class IA, Bandung District Court Class IA, Bale Bandung District Class IA and Garut District Court. Secondary data for this research were obtained from a literature study of laws and regulations governing the Small Claim Court procedure. Based on the results of the research, there are several problems related to the application of the Regulation on Small Claim Court related to the binding power of the use of the Small Claim Court, the use of a single judge in deciding, the problem of domicile differences. These problems can be minimized with several efforts to resolve them properly and effectively so that the application of the principles of fast, simple and low cost justice in a Small Claim Court is not only a mere slogan without any real realization.